(3eONd dOQGSI GdJShjb GdMOjKs - (3GjGO YHO GdaJGM(B, (3GdfShQs ((3YeGf(B:s (3OGQ UaGA(B,s, 2011)
(3ebOeI aj GdJMdjd Gdcej h feGPL GdGfMOGQ GdKfGFj , GdGfMOGQ GdeJYOO , GdefGgL GdcejI aj GdJSYjQ , GdJfHD HGdcdH , SdGSd eGQcha h GNJjGQ GdShb , feGPL fXQjI GdGfJXGQ , feGPL eTGcd Gdfbd h feGPL eTGcd GdJYjjf , bVGjG aj OQGSI Sdhc GdeSJgdc(B.s
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdJMdjd Gdcejs; (3GdJShjbs